Representasi Iman dalam Film Kafir: Analisis Semiotika Ferdinand De Saussure - Fauziah, Wifkiyah; Malik, Saeful (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This paper discusses the representation of faith in the infidel film of 2018. The background of this study is the lack of religion that occurs in society today. People who forget their God and forget themselves. The lack of religion in society today makes them complacent about the sparkling world that makes them forget to think long. A person can justify any means to get what he wants. They will bear all the risks as long as their wishes can come true. Without them knowing they are being enslaved by the things of the world. A small example, jealous when you see the happiness of others. So that this jealousy raises the intention to get the same or more happiness, sometimes by justifying all means, including with the help of the supernatural power of a shaman or performing the ritual of the ritual on his own. This study aims to determine the faith contained in the film Kafir. This film has religious nuances so the writer is interested in exploring the faith that is contained in it. This research is a type of qualitative research with the semiotic analysis method of Ferdinand De Saussure which focuses on what is Signifier, Signified in Kafir Films and what is social reality in Kafir Films. Semiotics of Ferdinand De Saussure is used to analyze each scene that displays faith. The results showed that: The concept of faith in a film can attract the attention of the audience because the film has the power to entertain. As is the case with faith that is packaged in a pagan film. Even though this film is a horror type, it is not just scary like other films, but this film contains religious nuances, there are wisdom values contained, such as: 1) Faith in qada and qadar Allah. The meanings of signifier and signified are described by the characters Sri, Andi and Dina who apply tawakal to Allah and believe that their father has been called by Allah. 2) Faith in God's books. The meaning of the signifier and the signified is described by the character Sri with the reading of the holy al-Qur'an verse to protect himself